2022
DOI: 10.3389/fnut.2022.862974
|View full text |Cite
|
Sign up to set email alerts
|

Galactooligosaccharide Treatment Alleviates DSS-Induced Colonic Inflammation in Caco-2 Cell Model

Abstract: The biological activities of dietary bioactive polysaccharides have been largely explored. Studies on the immunomodulating effects of oligosaccharides and polysaccharides have shown that they are able to modulate innate immunity. Prebiotics are a class of poorly digested carbohydrates that are mainly produced from dietary fibers, which are carbohydrate polymers with ten or more monomeric units as defined by the Codex Alimentarius Commission in 2009. Considering the capacity of prebiotics in reducing gut inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…DSS administration can reportedly cause a decrease in the colon length because DSS causes redistribution of tight junctions, resulting in increased cell permeability, which in turn increases inflammatory cytokines, causing inflammation in the intestinal tissue, and destroying intestinal tissue cells. 28,46 In the DSS treatment groups, the colon lengths were significantly reduced, and PCA administration reversed this phenotype in a dose-dependently manner (Fig. 6B).…”
Section: Pca Alleviates Dss-induced Inflammatory Bowel Disease In Vivomentioning
confidence: 89%
“…DSS administration can reportedly cause a decrease in the colon length because DSS causes redistribution of tight junctions, resulting in increased cell permeability, which in turn increases inflammatory cytokines, causing inflammation in the intestinal tissue, and destroying intestinal tissue cells. 28,46 In the DSS treatment groups, the colon lengths were significantly reduced, and PCA administration reversed this phenotype in a dose-dependently manner (Fig. 6B).…”
Section: Pca Alleviates Dss-induced Inflammatory Bowel Disease In Vivomentioning
confidence: 89%
“…Nevertheless, the maternal will undergo metabolic syndrome during normal pregnancy, especially in late gestation, which decreases dramatically gut microbiota diversity and richness ( Collado et al, 2010 ; Cheng et al, 2018 ). Recent studies showed that GOS had the promising potential to alleviate metabolic diseases by regulating the intestinal flora ( Silk et al, 2009 ; Roselli et al, 2022 ). The dominating prebiotic functions of GOS are to selectively stimulate probiotic proliferation ( Bifidobacteria , Bacteroides ) and to produce short-chain fatty acids by fermenting ( Li et al, 2015 ; Vulevic et al, 2015 ; Grimaldi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, current study was undertaken to examine epithelial-intrinsic effects of claudin-2 expression under conditions of colitis/stress. Recent studies have used similar in vitro treatment of IECs by DSS to model colitis-induced epithelial injury 44 47 . However, both, DSS treatment and starvation resulted in a similar fate for claudin-2 and IECs survival, which suggest that the autophagy-mediated regulation of claudin-2 may not be limited to IBD.…”
Section: Discussionmentioning
confidence: 99%